The questionable economics of development assistance in Africa: hot-fresh evidence, 1996-2010 - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This paper assesses the aid-development nexus in 52 African countries using updated data (1996-2010) and a new indicator of human development (adjusted for inequality). The effects of Total Net Official Development Assistance (NODA), NODA from the Development Assistance Committee (DAC) and NODA from Multilateral donors on economic prosperity (at national and per capita levels) are also examined. The findings broadly indicate that development assistance is detrimental to GDP growth, GDP per capita growth and inequality adjusted human development. The magnitude of negativity (which is consistent across specifications and development dynamics) is highest for NODA from Multilateral donors, followed by NODA from DAC countries. Given concerns on the achievement of the MDGs, the relevance of these results point to the deficiency of foreign aid as a sustainable cure to poverty in Africa. Though the stated intents or purposes of aid are socio-economic, the actual impact from the findings negates this. It is a momentous epoque to solve the second tragedy of foreign aid; it is high time economists and policy makers start rethinking the models and theories on which foreign aid is based. In the meantime, it is up to people who care about the poor to hold aid agencies accountable for piecemeal results. Policy implications and caveats are discussed.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa